Identification of 1, 2, 4-Triazine and Its Derivatives Against Lanosterol 14-Demethylase (CYP51) Property of Candida albicans: Influence on the Development of New Antifungal Therapeutic Strategies - Verma, Abhishek Kumar; Majid, Aarfah; Hossain, Md. Shahadat; Ahmed, SK. Faisal; Ashid, Mohammad; Bhojiya, Ali Asger; Upadhyay, Sudhir K.; Vishvakarma, Naveen Kumar; Alam, Mudassir (Frontiers in Medical Technology, 2022)
This research aims to find out whether the 1, 2, 4-triazine and its derivatives have antifungal effects and can protect humans from infection with Candida albicans. Molecular docking and molecular dynamic simulation are widely used in modern drug design to target a particular protein with a ligand. We are interested in using molecular docking and molecular dynamics modeling to investigate the interaction between the derivatives of 1, 2, 4-triazine with enzyme Lanosterol 14-demethylase (CYP51) of Candida albicans. The inhibition of Candida albicans CYP51 is the main goal of our research. The 1, 2, 4-triazine and its derivatives have been docked to the CYP51 enzyme, which is involved in Candida albicans Multidrug Drug Resistance (MDR). Autodock tools were used to identify the binding affinities of molecules against the target proteins. Compared to conventional fluconazole, the molecular docking results indicated that each drug has a high binding affinity for CYP51 proteins and forms unbound interactions and hydrogen bonds with their active residues and surrounding allosteric residues. The docking contacts were made using a 10 ns MD simulation with nine molecules. RMSD, RMSF, hydrogen bonds, and the Rg all confirm these conclusions. In addition, these compounds were expected to have a favorable pharmacological profile and low toxicity. The compounds are being offered as scaffolds for the development of new antifungal drugs and as candidates for future in vitro testing.